Polymer interlayer with improved optical capabilities

JP2026534161APending Publication Date: 2026-10-14SOLUTIA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026517311
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-18
Filing Date
2024-09-17
Publication Date
2026-10-14

Smart Images

  • Figure 2026534161000001_ABST
    Figure 2026534161000001_ABST
Patent Text Reader

Abstract

An intermediate layer is disclosed, which is at least a double layer, for use as a component for an electromagnetically reflective intermediate layer. The intermediate layer comprises a first layer including a reflective layer, and a second layer including a PVB resin that is plasticized with a plasticizer to form plasticized PVB, wherein the second layer has a flow value DF135 of 145 μm or less, and the PVB of the second layer has a polydispersity index (PDI) greater than 4.2. Electromagnetically reflective intermediate layers and multilayer rigid laminated composite materials are also described.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001]

[0001] The present invention relates to the field of polymer interlayers and interlayer components, and more specifically, to polymer interlayers useful for the manufacture of laminated glass composites.

Background Art

[0002]

[0002] Angstrom-thick or thicker layers of metals, metal compounds, and other active agents have conventionally been used in multilayer glass panels to reflect infrared solar radiation that generates heat while transmitting visible light. These layers can be arranged sequentially as a stack, and can be disposed on any suitable substrate such as a biaxially stretched thermoplastic poly(ethylene terephthalate) (PET) film or similar material. One form, known as an interference filter, comprises at least one reflective metal layer sandwiched between anti-reflective or antireflective dielectric layers.

[0003]

[0003] When an IR reflective film such as an interference filter is combined with glass in a multilayer glass laminate, for example in a vehicle windshield, it typically includes plasticized poly(vinyl butyral) (PVB) as at least one impact-dispersing interlayer, which absorbs impact from the head of an occupant inside the vehicle or foreign matter from outside the vehicle, and prevents penetration through the windshield. In a typical arrangement, a single layer of coated reflective film of the poly(ethylene terephthalate) type is disposed between two layers of poly(vinyl butyral) type material to form a three-layer structure, which is then disposed between two layers of glass. The finished multilayer glass composite has the combined advantages of safety and controlled electromagnetic radiation transmission.

[0004]

[0004] Certain challenges may arise in the process of manufacturing these intermediate layers and related multilayer composite materials, including intermediate layers sandwiched between rigid substrates such as glass. For example, processing conditions in the lamination process of glass composites may result in one or more of the following: shrinkage of the IR reflective film, so-called "short vinyl" where vinyl is pulled from the edges of the glass before it bonds to the glass, and problems in achieving proper "edge loss" to avoid the risk of corrosion of the infrared radiation reflective layer. In the finished glass composite, each of these can cause delamination, optical problems, and defects in other products, which are unacceptable.

[0005]

[0005] Additional optical quality defects that may be particularly noticeable when viewed from an oblique angle may occur in such safety glass panels as visually apparent isotropic wavy reflections with an estimated amplitude of about 0.002–0.012 mm and a wavelength of 2.5–7.5 mm. This is referred to in the Art and hereafter as “applesake”. Several theories have been proposed regarding the cause of applesake. As described in U.S. Patent No. 9,452,958 assigned to an entity relating to the assignee of the present invention, applesake may occur because a polyethylene-type layer that reflects light when viewed from an oblique angle follows a poly(vinyl butyral)-type layer between the laminates, taking the form of nonlinearity, also called wavy or nonplanar, which may be present in the poly(vinyl butyral)-type layer.

[0006]

[0006] Several attempts have been reported to mitigate the severity of applesauce (see, for example, U.S. Patents 4,465,736, 4,973,511, 6,455,141, 5,091,258, and 9,248,628). However, further methods are needed to reduce applesauce. Thus, there is a need for further improved compositions and methods to enhance the properties of polymer film layers, particularly polymers and poly(vinyl butyral) sheets used in combination with poly(ethylene terephthalate), without adversely affecting the optical properties and other required performance characteristics of the resulting laminated glass composites. [Overview of the Initiative]

[0007]

[0007] In one embodiment, the present invention relates to a double layer for use as a component for an electromagnetically reflective intermediate layer. The double layer comprises a first layer including an electromagnetic energy reflective layer, wherein the reflective layer of the electromagnetic energy reflective layer includes a base surface and an upper surface, and a second layer having a thickness of 0.3 to 0.55 mm and including a PVB resin that has been plasticized with a plasticizer to form a plasticized PVB, wherein the second layer has a contact surface adjacent to the upper surface of the electromagnetic energy reflective layer, and (a) the second layer has a flow value DF135 of 145 μm or less, and (b) the PVB of the second layer has a PDI greater than 4.2.

[0008]

[0008] In one embodiment, the present invention relates to an electromagnetically reflective multilayer intermediate layer for a multilayer laminated rigid composite material. The electromagnetically reflective multilayer intermediate layer includes: a first layer comprising an electromagnetic energy reflective layer, wherein the reflective layer of the electromagnetic energy reflective layer comprises a base surface and an upper surface; a second layer having a thickness of 0.3 to 0.55 mm and comprising a PVB resin plasticized with a plasticizer to form a plasticizable PVB, wherein the second layer has a contact surface adjacent to the upper surface of the electromagnetic energy reflective layer; and a third layer comprising PVB plasticized with a plasticizer to form a plasticizable PVB, wherein the third layer has a contact surface adjacent to the base surface of the reflective layer of the energy reflective layer, and (a) the second layer has a flow value DF135 of 145 μm or less; and (b) the PVB of the second layer has a PDI greater than 4.2.

[0009]

[0009] In one embodiment, the present invention relates to a multilayer rigid laminated composite material. The multilayer rigid laminated composite material of the present invention includes an electromagnetically reflective intermediate layer of the present invention sandwiched between a first rigid sheet and a second rigid sheet. The laminated composite structure can be characterized by a ROSA score of 125 pixels or less.

[0010]

[0010] Other aspects of the present invention are disclosed and claimed herein. [Brief explanation of the drawing]

[0011] [Figure 1]

[0011] This is a partial cross-sectional view of an exemplary embodiment of the double layer of the present invention. [Figure 2]

[0012] This is a partial cross-sectional view of an exemplary embodiment of the electromagnetically reflective intermediate layer of the present invention. [Figure 3]

[0013] This is a partial cross-sectional view of an exemplary embodiment of the multilayer rigid laminated composite material of the present invention. [Figure 4]

[0014] This is a schematic diagram of an exemplary apparatus for analyzing the ROSA score of multilayer rigid laminated composite materials. [Modes for carrying out the invention]

[0012]

[0015] To facilitate a more comprehensive understanding of this specification, the meanings of certain terms and / or phrases used herein are set forth or defined below. Nevertheless, the definitions and explanations should be received or interpreted not to limit these terms to what would be understood by those skilled in the art, but merely to improve the understanding of how certain terms are used herein.

[0013]

[0016] As used herein, the terms “polymer intermediate layer,” “interlayer,” “polymer layer,” “layer,” and “sheet” may refer to a single-layer sheet or a multilayer assembly. A “single-layer sheet,” as its name suggests, is a single polymer layer extruded as a single layer. A “double layer” refers to at least two but optionally more layers, including separately extruded layers, co-extruded layers, or any combination of separately co-extruded and co-extruded layers. A multilayer assembly may include multiple layers, including separately extruded layers, co-extruded layers, or any combination of separately extruded and co-extruded layers. As a non-limiting example, a multilayer intermediate layer sheet may be, for example, a combination of two or more single-layer sheets ("multilayer sheet"), two or more co-extruded layers ("co-extruded sheet"), a combination of two or more co-extruded sheets, a combination of at least one single-layer sheet and at least one co-extruded sheet, and a combination of at least one multilayer sheet and at least one co-extruded sheet. In various embodiments of the present invention, the multilayer intermediate layer comprises at least two polymer layers (e.g., a single layer or multiple co-extruded layers) arranged in contact with each other and each containing a polymer resin.

[0014]

[0017] As used herein, the term “resin” refers to the polymer component of a layer or polymer layer (e.g., poly(vinyl acetal), such as poly(vinyl butyral), often referred to as PVB). Typically, resins can be combined with plasticizers, as will be discussed in more detail below, to produce plasticized polymers, such as plasticized PVBs. Furthermore, as illustrated herein, plasticized resins may have other components or elements in addition to the polymer or resin and plasticizer.

[0015]

[0018] The term “adjacent” is used herein to describe the spatial relationship between elements such as coatings, surfaces, or layers, including such elements that are in contact with or adjacent to one another, as well as elements that may be indirectly connected to each other, even though they are separated by one or more coatings, films, or additional layers. In contrast, “contact” is intended to describe elements that are in direct physical contact.

[0016]

[0019] While polyvinyl butyral ("PVB") may be specifically discussed as a polymer resin for polymer layers or intermediate layers in this application, it should be understood that other thermoplastic resins besides PVB are intended and are included in the spirit and scope of the present invention. The resins or polymers envisioned include, but are not limited to, polyurethane, polyvinyl chloride, poly(ethylene vinyl acetate), and combinations thereof. These polymers can be used alone or in combination with other polymers. Therefore, where ranges, values, properties and / or methods (e.g., proportion of plasticizer components, thickness, and property-enhancing additives) are given herein for elements such as PVB resins or layers, it should be understood that these ranges, values, and / or methods, where applicable, are also applicable to other polymers and polymer blends disclosed herein, or can be modified to be applicable to different materials, as is known to those skilled in the art.

[0017]

[0020] In one embodiment, the present invention relates to a bilayer that is useful or usable as a component of an electromagnetically reflective interlayer. The electromagnetically reflective interlayer may therefore be useful or usable as an interlayer for a laminated composite in which the interlayer is sandwiched between two rigid sheets. Referring to Figure 1, the bilayer 5 may include a first layer 10 and a second layer 20. The first layer 10 may include an electromagnetic energy reflective layer, or be referred to as an electromagnetic energy reflective layer, and may include a base surface 13 and a top surface 15. In one or more exemplary embodiments, the first layer 10 may have a thickness of about 12 microns to about 125 microns. In one or more exemplary embodiments, the electromagnetic energy reflective layer 10 includes a substrate 12 having a base surface 13 and a coating surface 14 supporting an electromagnetic energy reflective coating 16. The substrate 12 may be formed from any suitable film-forming polymer. Suitable polymers for forming the substrate 12 may include polyesters such as polyethylene terephthalate (PET), polycarbonates, polyamides, and the like. The substrate may have a thickness of approximately 12 to 125 microns or 25 to 76 microns.

[0018]

[0021] The electromagnetic energy reflective coating 16 on the upper surface of the first layer 10 or the coating surface 14 may be a single layer or multilayer coating of any material that reflects incident electromagnetic energy. In one or more exemplary embodiments, the electromagnetic energy reflective coating 16 may have a thickness of about 10 nm to 250 nm. In one or more exemplary embodiments, the electromagnetic energy reflective coating 16, or more generally the reflective layer 10, reflects electromagnetic energy in the visible range, the infrared range, or the wavelength range of 780 nm to 2,500 nm. In one or more exemplary embodiments, the coating may include a metal layer, a metal oxide layer, or a combination thereof, or multiple metal layers, multiple metal oxide layers, or a combination thereof. In one or more exemplary embodiments, the electromagnetic energy reflective coating 16 includes layers in which high refractive index material and low refractive index material are alternated.

[0019]

[0022] Electromagnetic energy reflective coating 16 and, in applicable embodiments, its various layers may be formed from or applied to substrate 12 using known, commonly available coating deposition techniques. Non-limiting examples of suitable coating deposition techniques include sputtering, vacuum deposition, solvent or solution coating, and the like. The electromagnetic energy reflective coating 16 may be a vacuum-deposited coating, meaning that the coating layer or (in multi-layer coating embodiments) all layers of the coating are deposited via vacuum deposition.

[0020]

[0023] In one or more exemplary embodiments, the reflective layer may be a coated reflective film. Such reflective films are known in the art and are commercially available, for example, from the assignee of the present invention under the trade name XIR™. Suitable reflective films and their structures are also described, for example, in U.S. Patent No. 10,946,619, the content and disclosure of which are incorporated herein by reference.

[0021]

[0024] In one or more exemplary embodiments, the electromagnetic energy reflective layer 10 comprises alternating multilayer organic refractive index structures, as described for example in U.S. Patent No. 5,103,337, the content and disclosure of which are incorporated herein by reference.

[0022]

[0025] The bilayer of the present invention may include a second layer 20 comprising a contact surface 21 in contact with the upper surface 15 of the reflective layer 10. The second layer 20 may comprise a PVB resin that is plasticized with a plasticizer to form plasticized PVB. The second layer may have a thickness of 0.30 to 0.55 mm. In one or more exemplary embodiments, the second layer 20 has a flow value DF135 of 145 μm or less, or 142 μm or less, or 140 μm or less, or 135 μm or less, or 130 μm or less, or 120 μm or less, or 110 μm or less, or 100 μm or less, or 90 μm or less, or 80 μm or less, or 75 μm or less, or 70 μm or less, or 60 μm to 145 μm, or 60 μm to 135 μm, or 60 μm to 130 μm, or 60 μm to 120 μm, or 60 μm to 100 μm, or 60 μm to 90 μm, or 60 μm to 80 μm, or 60 μm to 70 μm. In general, DF135 is a quantitative parameter related to a test protocol for quantifying or describing the flow of a bilayer or interlayer under simulated lamination conditions, and a higher DF135 value generally indicates better flow during autoclave lamination conditions. In analyzing the flow characteristics of the present invention, DF135 was measured as the deformation (reduction in sample thickness normalized according to a standard interlayer thickness of 0.76 mm) when a specific load pressure (i.e., 11.5 psi) was applied to the sample surface in the thickness direction and the sample was heated from 23°C to 140°C at a heating rate of 10°C / min. Flow is generally measured as DF135 by a thermomechanical analyzer. As an example, a sheet sample with a thickness of 0.76 mm is cut into a disc with a diameter of 8 mm, and this disc is subjected to the DF135 test. A flow value of 0.242 mm means that the interlayer with a thickness of 0.76 mm deforms by 0.242 mm in the thickness direction. The flow value is calculated by subtracting the thickness at 135°C from the thickness at 45°C, which was measured under the aforementioned conditions to obtain the deformation value. This value is then normalized to a standard interlayer thickness of 0.76 mm.

[0023]

[0026] In one or more exemplary embodiments, the contact surface 21 of the second layer 20 may have a surface roughness value Rz of less than 45 μm, or less than 35 μm, or less than 25 μm, or less than 20 μm, or less than 15 μm. The second layer 20 may also include a laminate surface 22 on the opposite side of the contact surface 21, and in one or more embodiments, the laminate surface may have an Rz value of 20 μm or more. Generally, Rz is a known quantification parameter in commercially available test protocols for quantifying or describing surface roughness with respect to the peak height of the surface. When measuring the surface roughness Rz of the contact surface 21 of the present invention, and also to measure the MD Rsm described below, the surface roughness was measured using a Mahr M1 500 Perthometer, and each sample was measured on both the top and bottom surfaces of the sample. In addition, five traces were performed at each measurement position in both the machine direction and the orthogonal machine direction. The surface roughness value Rz recorded in the examples is the average value obtained from both directions on the top or bottom surface of the sheet, while MD Rsm is the average value in the machine direction.

[0024]

[0027] In one or more exemplary embodiments, the contact surface 21 of the second layer 20 may have a machine direction surface roughness value (MD Rsm) of 200 to 900 or less than 1000. Generally, MD Rsm is a known quantification parameter relating to commercially available test protocols that quantifies or describes surface roughness in relation to the distance between surface peaks. The recorded surface roughness value MD Rsm was the average value obtained from five machine direction (MD) measurements on the top or bottom surface of the sheet.

[0025]

[0028] In one or more exemplary embodiments, the contact surface of the second layer is a non-embossed surface such that the surface roughness is created solely by a known melt-factoring method or technique. In one or more exemplary embodiments, the contact surface of the second layer is an embossed surface such that the surface roughness is created by a combination of a known embossing method or technique and a known melt-factoring method or technique.

[0026]

[0029] In one or more exemplary embodiments, the second layer has a warm shrinkage of 8% or less. Generally, the term “warm shrinkage” is intended to describe the change in dimensions of a layer, sheet, or film after exposure to a temperature of 54°C for 10 minutes. For the purposes of the present invention, warm shrinkage was measured using the following protocol: A 20 cm sheet-like sample was cut from the extruded layer roll immediately after extrusion, measured in the machine direction using a calibrated ruler, marked using a template to indicate a distance of 10 cm from the edge in the machine direction as the original length of the sample, and then placed on a cardboard sheet. The sample on the cardboard was placed on a shelf in a furnace pre-set to a temperature of 54°C. The sample was then removed from the furnace after 10 minutes and placed on a workbench to cool to room temperature over at least 5 minutes. The length of the sample in the machine direction was measured using a calibrated ruler before and after processing in the 54°C furnace. Shrinkage was calculated as the percentage change in length in the machine direction relative to the original length before processing in the furnace.

[0027]

[0030] The second layer 20 contains a PVB resin. The PVB resin of the second layer can be produced by known aqueous or solvent acetalization processes, which involve reacting polyvinyl alcohol ("PVOH") with butyraldehyde in the presence of an acid catalyst, followed by separation, stabilization, and drying of the resin. Such acetalization processes are described, for example, in U.S. Patents 2,282,057 and 2,282,026, and in Wade, B. (2016), “Vinyl Acetal Polymers”, Encyclopedia of Polymer Science and Technology This is disclosed in pp. 1–22 (John Wiley & Sons, Inc.), and the entire disclosures of these documents are incorporated herein by reference.

[0028]

[0031] In this specification, the terms "poly(vinyl acetal)" or "poly(vinyl butyral)" are used in general, but the PVB resins described herein may contain, but are not limited to, any suitable aldehyde residues including isobutyraldehyde. In some embodiments, one or more poly(vinyl acetal) resins contain at least one C1-C 10The compound may contain an aldehyde or at least one C4-C8 aldehyde residue. Suitable examples of C4-C8 aldehydes may include, but are not limited to, n-butyraldehyde, isobutyraldehyde, 2-methylbarrelaldehyde, n-hexylaldehyde, 2-ethylhexylaldehyde, n-octylaldehyde, and combinations thereof.

[0029]

[0032] A useful parameter for describing the PVB resin components of the present invention is the residual hydroxyl group content (as vinyl hydroxyl group content or poly(vinyl alcohol) (PVOH) content). Residual hydroxyl content refers to the amount of hydroxyl groups remaining as side groups on the polymer chain after the processing is complete. For example, PVB can be produced by hydrolyzing poly(vinyl acetate) to poly(vinyl alcohol), and then reacting this poly(vinyl alcohol) with butyraldehyde to form PVB. In the process of hydrolyzing poly(vinyl acetate), not all acetate side groups are usually converted to hydroxyl groups. Furthermore, in the reaction with butyraldehyde, not all hydroxyl groups are usually converted to acetal groups. As a result, in any completed PVB, residual acetate groups (such as vinyl acetate groups) and residual hydroxyl groups (such as vinyl hydroxyl groups) are usually present as side groups on the polymer chain. In general, among the variables in the polymer manufacturing process, the residual hydroxyl content of the polymer can be adjusted by controlling the reaction time and reactant concentration. When used as a parameter in this specification, the residual hydroxyl content is measured in weight percent according to ASTM D-1396.

[0030]

[0033] In various embodiments, the PVB resin contains approximately 8 to approximately 35 wt% residual hydroxyl groups calculated as PVOH, approximately 13 to approximately 30 wt% residual hydroxyl groups calculated as PVOH, approximately 8 to approximately 22 wt% residual hydroxyl groups calculated as PVOH, or approximately 15 to approximately 22 wt% residual hydroxyl groups calculated as PVOH. With respect to the high-rigidity intermediate layers disclosed herein, in one or more layers, the poly(vinyl butyral) resin contains more than approximately 19 wt% residual hydroxyl groups calculated as PVOH, more than approximately 20 wt% residual hydroxyl groups calculated as PVOH, more than approximately 20.4 wt% residual hydroxyl groups calculated as PVOH, and more than approximately 21 wt% residual hydroxyl groups calculated as PVOH.

[0031]

[0034] In various embodiments, the PVB resin contains a residual hydroxyl content of at least about 18, at least about 18.5, at least about 18.7, at least about 19, at least about 19.5, at least about 20, at least about 20.5, at least about 21, at least about 21.5, at least about 22, at least about 22.5 wt%, and / or about 30 or less, about 29 or less, about 28 or less, about 27 or less, about 26 or less, about 25 or less, about 24 or less, about 23 or less, or about 22 wt%.

[0032]

[0035] Furthermore, the resin may be a polyvinyl ester with residual ester groups calculated as acetates in amounts of less than 35 wt%, less than 30 wt%, less than 25 wt%, less than 15 wt%, less than 13 wt%, less than 11 wt%, less than 9 wt%, less than 7 wt%, less than 5 wt%, or less than 1 wt%, with the remainder being acetal, preferably butyraldehyde acetal, but possibly containing trace amounts of other acetal groups, such as 2-ethylhexanal groups (see, for example, U.S. Patent No. 5,137,954, the entire disclosure of which is incorporated herein by reference). The residual acetate content of the resin can also be measured in accordance with ASTM D-1396.

[0033]

[0036] In some embodiments, as described above, one or more of the polymer layers of the intermediate layer may be formed from a poly(vinyl acetal) resin. Such a poly(vinyl acetal) resin may have a residual acetate content, as measured above, of at least about 1, at least about 3, at least about 5, at least about 7 wt%, and / or about 15 or less, about 12 or less, about 10 or less, or about 8 wt% or less.

[0034]

[0037] Other parameters useful in describing the PVB resin components of the present invention relate to their molecular weight. As is known in the art, molecular weight can be quantified as weight-average molecular weight (Mw) or number-average molecular weight (Mn). The weight-average molecular weight of the PVB resins of the present invention can range from about 50,000 to about 600,000, about 70,000 to about 450,000, or about 100,000 to about 425,000, or about 180,000 to about 250,000 Daltons. A related parameter, the polydispersity index (PDI), characterizes the particle size distribution of the sample and is calculated as the ratio of weight-average to number-average molecular weight (Mw / Mn). The PVB resins of the present invention may have a PDI greater than 2.5, or greater than 3.0, or greater than 3.5, or greater than 4.0, or greater than 4.2, or between 2.5 and 7.0, or between 4.0 and 7.0. For the tests described herein, the molecular weight (kg / mol) of the PVB resin was measured at 40°C by gel permeation chromatography (GPC) in hexafluoroisopropanol (HFIP solvent) containing 20 mM potassium trifluoroacetate. (Flow rate: 1.0 ml / min, sample solution: 20 mg of sample in 10 ml of hexafluoroisopropanol containing 20 mM potassium trifluoroacetate + 10 μl of isopropanol flow marker, injection volume: 10 μl, column set: Polymer Laboratories 5 μm HFIP gel guard and Mixed HFIP gel). Further details of the detection and instrumentation are as follows: In the detection section, the refractive index was set to 40°C, the decay was set to 31250 nRIU, and the zero offset was set to 5%. The calibrator was a monodisperse polymethyl methacrylate standard with Mw ranging from 580 to 3,000,000 g / mol.

[0035]

[0038] The second layer, and other components or elements of the present invention, include a PVB resin that is plasticized with a plasticizer to form plasticized PVB. Generally, in the formation of a polymer layer or intermediate layer, a plasticizer may be added to the polymer resin, for example, to increase the flexibility or durability of the resulting product. Plasticizers generally work by being incorporated between polymer chains to increase the spacing between chains ("free volume"), thereby lowering the glass transition temperature (T) of the polymer resin. g It significantly lowers the glass transition temperature (T) of the plasticizer in the second layer, which softens the material. In this regard, the amount of plasticizer in the second layer is related to the glass transition temperature (T) of the plasticized PVB. g The glass transition temperature (T) can be adjusted and set to the desired value. g ) is the temperature at which the intermediate layer transitions from a glassy state to a rubbery state. Generally, the higher the amount of plasticizer added, the higher the temperature. g It can be lower.

[0036]

[0039] Suitable plasticizers for the second layer of plasticized PVB generally include, but are not limited to, polymeric plasticizers such as esters of polybasic acids, polyhydric alcohols, triethylene glycol di-(2-ethyl butyrate), triethylene glycol di-(2-ethylhexanoate) (known as "3-GEH"), triethylene glycol diheptanoate, tetraethylene glycol diheptanoate, dihexyl adipate, dioctyl adipate, hexylcyclohexyl adipate, mixtures of heptyl adipate and nonyl adipate, diisononyl adipate, heptylnonyl adipate, dibutyl sebacate, oil-modified alkyd sebacate, and mixtures of phosphates and adipates, as well as mixtures and combinations thereof. 3-GEH is particularly preferred. Other suitable plasticizers may include, but are not limited to, tetraethylene glycol di(2-ethylhexanoate) ("4-GEH"), di(butoxyethyl) adipate, bis(2-(2-butoxyethoxy)ethyl) adipate, dioctyl sebacate, nonylphenyltetraethylene glycol, and mixtures thereof.

[0037]

[0040] Other suitable plasticizers may include, but are not limited to, blends of two or more different plasticizers, including the plasticizers described above. Further suitable plasticizers, or blends of plasticizers, may be formed from aromatic groups, such as polyadipates, epoxides, phthalates, terephthalates, benzoates, toluates, melitates, and other specialty plasticizers. Further examples include, but are not limited to, dipropylene glycol dibenzoate, tripropylene glycol dibenzoate, polypropylene glycol dibenzoate, isodecyl benzoate, 2-ethylhexyl benzoate, diethylene glycol benzoate, propylene glycol dibenzoate, 2,2,4-trimethyl-1,3-pentanediol dibenzoate, 2,2,4-trimethyl-1,3-pentanediol benzoate isobutyrate, 1,3-butanediol dibenzoate, diethylene glycol di-o-toluate, triethylene glycol di-o-toluate, dipropylene glycol di-o-toluate, 1,2-octyl dibenzoate, tri-2-ethylhexyl trimellitate, di-2-ethylhexyl terephthalate, bisphenol A bis(2-ethylhexanoate), ethoxylated nonylphenol, and mixtures thereof. In some embodiments, the plasticizer can be selected from the group consisting of dipropylene glycol dibenzoate, tripylene glycol dibenzoate, and combinations thereof.

[0038]

[0041] Generally, the plasticizer content of plasticized PVB resin can be technically measured in weight ratio, in parts per 100 parts of resin ("phr"), in the polymer layer and intermediate layer. For example, when 30 grams of plasticizer are added to 100 grams of polymer resin, the plasticizer content of the resulting plasticized polymer is 30 phr. Where the plasticizer content of a polymer layer is indicated in this application, the plasticizer content of that particular layer is determined based on the phr of the plasticizer in the molten material used to produce that particular layer.

[0039]

[0042] In one or more exemplary embodiments, the second layer of the bilayer of the present invention may have a total plasticizer content of 40 phr or less, or 38 phr or less, or 36 phr or less, or 34 phr or less, or 32 phr or less, or 30 phr or less. In some embodiments, the total plasticizer content of the second layer of the bilayer can be about 18 to about 40 phr, about 20 to about 38 phr, or about 25 to about 35 phr.

[0040]

[0043] As described above, another parameter that may be useful in describing the plasticized PVB of the present invention is the glass transition temperature (T g ) . As is known in the art, the glass transition temperature can be measured by dynamic mechanical thermal analysis (DMTA) in shear mode, which measures the storage (elastic) modulus (G'), loss (viscosity) coefficient (G"), and tan delta (=G' / G') of the specimen as a function of temperature at a given vibration frequency and temperature sweep rate. Next, T g This is determined by the position of the tan delta peak on a temperature scale in °C, and the peak value of the tan delta is sometimes referred to as tan delta or peak tan delta. In quantifying the glass transition temperature of the present invention, a frequency of 1 Hz and a temperature sweep rate of 3 °C / min were used. As used herein, "tan delta," "peak tan delta," "tan δ," and "peak tan δ" may be used interchangeably. In one or more exemplary embodiments, the plasticized PVB resin of the present invention has a glass transition temperature of less than 40 °C, less than 39 °C, less than 38 °C, or between 30 and 40 °C, greater than 32 °C, greater than 35 °C, or between 31 and 38 °C.

[0041]

[0044] Plasticized PVB may contain one or more additional and / or optional components. For example, adhesion control agents ("ACAs") may also be added to plasticized PVB. ACAs generally serve to modify and / or improve the adhesion of an intermediate layer to a rigid sheet, such as glass, when forming laminated composites. Possible ACAs include, but are not limited to, magnesium carboxylates / salts. Other possible ACAs include those disclosed in U.S. Patent No. 5,728,472, which is incorporated herein by reference in whole, such as residual sodium acetate, potassium acetate, and / or magnesium bis(2-ethylbutyrate).

[0042]

[0045] Other additives may be incorporated into the plasticized PVB to enhance its performance in the final product and / or impart certain additional properties. Such additives include, but are not limited to, dyes, pigments, stabilizers (e.g., UV stabilizers), antioxidants, antiblocking agents, flame retardants, IR absorbers or blockers (e.g., indium tin oxide, antimony tin oxide, lanthanum hexaboride (LaB6), and cesium tungsten oxide), processing aids, flow-promoting additives, lubricants, impact modifiers, nucleating agents, heat stabilizers, UV absorbers, UV stabilizers, dispersants, surfactants, chelating agents, coupling agents, adhesives, primers, reinforcing additives, and fillers, among other additives known to those skilled in the art.

[0043]

[0046] In another embodiment, the present invention relates to an electromagnetically reflective multilayer intermediate layer for multilayer laminated rigid composite materials. Referring to Figure 2, the intermediate layer 25 of the present invention includes a first layer 10 including a reflective layer, the reflective layer including a substrate 12 having a base surface 13 and a coating surface 14, and an electromagnetic energy reflective coating 16 on the coating surface 14 of the substrate 12; a second layer 20 including PVB plasticized with a plasticizer to form a plasticized PVB, the second layer 20 having a contact surface 21 adjacent to the electromagnetic energy reflective coating 16; and a third layer 30 including PVB plasticized with a plasticizer to form a plasticized PVB, the third layer having a contact surface 31 adjacent to the base surface 13 of the substrate. In one or more exemplary embodiments, the second layer has a flow value DF135 of 145 μm or less. In one or more embodiments, the PVB of the second layer has a PDI of at least 2.7 or at least 3.0 or at least 3.5. In one or more embodiments, the second layer 20 includes a laminate surface 22 on the opposite side of its contact surface 21, and the third layer 30 similarly includes a laminate surface 32 on the opposite side of its contact surface 31. One or both of the laminate surfaces 22 and 32 may have a surface roughness Rz of at least 20 μm.

[0044]

[0047] The third layer relative to the intermediate layer of the present invention can vary widely in form, features, or structure. In one or more exemplary embodiments, the third layer may be transparent or translucent. In one or more exemplary embodiments, the third layer may be colored or tinted. In one or more exemplary embodiments, the third layer may be a single layer or integrally molded sheet, or a multilayer assembly, multilayer sheet, co-extruded sheet), two or more co-extruded sheets combined together, a combination of at least one single layer sheet and at least one co-extruded sheet, and a combination of at least one multilayer sheet and at least one co-extruded sheet, or may include these. In one or more embodiments, the third layer may have a thickness of 0.3 mm to 1.3 mm. In one or more embodiments, the third layer may be a multilayer structure having sound attenuation properties, such as those described in U.S. Patent No. 9,460,702, the content and disclosure of which are incorporated herein by reference.

[0045]

[0048] For example, the above descriptions relating to the type and properties of the PVB resin, the type and amount of the plasticizer, the details of the plasticized PVB resin, and other elements of the second layer 20 may be the same as or different from those elements present in the third layer 30. More generally, and also to avoid doubt and to improve clarity of explanation, the present invention is described herein with respect to various interrelated aspects and embodiments, and those skilled in the art will understand and recognize that elements or features used to describe one aspect or embodiment may be applicable and useful when describing other embodiments. Accordingly, the descriptions and disclosures relating to elements or features of aspects or embodiments of the present invention are expressly relied upon herein to describe and support those elements or features in other aspects or embodiments. More specifically, the descriptions and disclosures relating to elements or features of the bilayers of the present invention, such as the PVB resin, plasticizer, and plasticized PVB described herein, are expressly relied upon herein to describe and support those elements or features in the electromagnetically reflective multilayer intermediate layers for laminated composite materials described herein, and vice versa.

[0046]

[0049] The second and third layers described herein, and more generally the double-layer structure and intermediate polymer, are assumed to be manufactured by any suitable process for producing polymer intermediate sheets that can be used in multilayer rigid composites (such as glass laminates), as is known to those skilled in the art. For example, the polymer intermediate sheet is assumed to be formed by solution casting, compression molding, injection molding, melt extrusion, melt blowing, or any other procedure known to those skilled in the art in the production and manufacture of polymer intermediate sheets. Furthermore, in embodiments utilizing multiple polymer intermediates, these multiple polymer intermediates are assumed to be formed by co-extrusion, inflation film, dip coating, solution coating, blade, paddle, air knife, printing, powder coating, spray coating, or any other process known to those skilled in the art. The final multilayer glass composite of this disclosure may be formed using processes known in the art.

[0047]

[0050] In one non-limiting method, the double layer 5 of the present invention may be pre-formed as an intermediate component of a multilayer intermediate layer, and as shown in Figure 2, the double layer may be combined with a second plasticized PVB resin sheet layer 30 and positioned in contact with the base surface 13 of the substrate 12 of the reflective layer 10, thereby forming a three-layer structure, which can then be positioned or sandwiched between two rigid sheets 40 and 50, as shown in Figure 3, to form a multilayer rigid laminated composite material 60. A preferred exemplary method of manufacturing in this regard is described in U.S. Patent No. 8,551,600, assigned to the assignee of the present invention, the contents and disclosures thereof of which are incorporated herein by reference.

[0048]

[0051] In an exemplary extrusion process, a thermoplastic resin and plasticizer, typically containing one of the resins and plasticizers described above, are pre-mixed and supplied to the extruder. Additives such as colorants and UV inhibitors (in liquid, powder, or pellet form) may be used and can be mixed with the thermoplastic resin or plasticizer before reaching the extruder. These additives, incorporated into the thermoplastic polymer resin and the resulting polymer sheet, enhance the specific properties of the polymer interlayer sheet and its ability to perform in the final multilayer composite product.

[0049]

[0052] In an extruder, the thermoplastic raw material and plasticizer particles, including any of the above-mentioned resins, plasticizers, and other additives, are further mixed and melted to form a molten material with a generally uniform temperature and composition. In embodiments of the present invention, the melting temperature may be about 200°C. When the molten material reaches the end of the extruder, it moves into the extruder die. The extruder die is a component of the extruder that gives the final product shape to the polymer interlayer sheet. The die typically has an opening defined by a lip, where the dimension in one direction is significantly larger than the dimension in the vertical direction. Generally, the die is designed so that the molten material flows uniformly and exits the die in the final shape of the product, starting from a cylindrical shape. Multiple shapes can be imparted to the final polymer interlayer sheet by the die, as long as the shape is continuous. Generally, in its most basic sense, extrusion is a process used to produce an object with a constant cross-sectional shape. This is achieved by pushing or pulling material through a die that has the desired cross-sectional shape of the final product.

[0050]

[0053] In another embodiment, the present invention relates to multilayer laminated rigid composites. Generally, the multilayer laminated rigid composites of the present invention include embodiments of the intermediate layer of the present invention, which is sandwiched between a first rigid sheet 40 and a second rigid sheet 50. The rigid sheets 40 and 50 may be inorganic, or may be formed from glass or a similar material, or may be organic, and may be formed from a polymer such as polycarbonate or acrylic. In one or more exemplary embodiments, the sheets 40 and 50 may have a thickness of 0.4 mm to 3.0 mm. In one or more embodiments, the thickness of the sheets 40 and 50 may be substantially constant along their length or may vary along their length. The rigid sheets may include coatings or additives to improve optical properties or toughness, such as infrared or UV absorbers. Referring to Figure 3, the multilayer rigid laminated composite material 60 includes a first layer 10 containing a reflective layer, a second layer 20 having a thickness of 0.3 to 0.55 mm and containing a PVB resin plasticized with a plasticizer to form a plasticizable PVB, wherein the second layer 20 has a laminate surface and a contact surface that contacts the electromagnetic energy reflective coating, a third layer 30 containing PVB plasticized with a plasticizer to form a plasticizable PVB, wherein the third layer has a laminate surface 32 and a contact surface 31 adjacent to the base surface 13 of the reflective layer of the energy reflective layer, a first rigid sheet 40 adjacent to the laminate surface 22 of the second layer 20, and a second rigid sheet 50 adjacent to the laminate surface 32 of the third layer 30.

[0051]

[0054] In one or more exemplary embodiments, the laminated rigid composite material may have a ROSA score of 125 pixels or less, or 110 pixels or less, or 90 pixels or less, or 80 pixels or less, or 75 pixels or less, or 70 pixels or less, or 25 to 145 pixels, or 25 to 125 pixels, or 35 to 125 pixels, or 45 to 125 pixels, or 50 to 125 pixels. The Reflectance Orange Skin Analyzer (ROSA) measurement method was developed to quantify the severity of "applesauce" (or orange skin / orange peel) using an oblique light reflection model. Referring to Figure 4, an LED light source was used to generate a signal and a camera was used to image the reflectance of the sample. The instrumentation includes a Smart Vision Lights S30-WHI-W Spot Light (LED, barrel type, 30mm, white, "Prox Light", wide-angle lens option, 24V) and a Balsler camera (avA1900-50gm, Aviator-KAI-02150, 2 / 3" C-Mount, 1920x1080, 51fps, mono, CCD, GigE) equipped with a Fujinon lens (HF12.5HA-1B, 12.5mm, 2 / 3" Format, C-Mount, manual focus, aperture, locking screw, aperture value 1.4). The instrumentation was configured so that the projector illuminated the sample at an oblique angle and the reflection was detected by the camera, as outlined in the schematic diagram of Figure 4. The measurements were performed in an enclosed area to block out other light sources besides the instrumentation's LED light. Reflection images of the sample from the tests described herein are shown in Figure 4.

[0052]

[0055] Next, the image analysis algorithm was applied to the reflected image. The image size is 1000 x 1000 pixels with horizontal dimensions of 65 x 65 mm. The grayscale image obtained from ROSA is transformed into an FFT (Fast Fourier Transform) of the image using a National Instruments Vision Development Module function called "IMAQ FFT". The FFT creates a complex image in which high frequencies are grouped in the center, while low frequencies are located at the edges. The FFT is then truncated using a National Instruments Vision Development Module function called "IMAQ Complex Truncate". The truncation frequency is set to 1.00%. The truncation frequency % is the percentage of frequencies retained in the Fourier transformed image. The function is set so that high-pass frequencies are truncated. The filtered FFT is inversely transformed back into the image using a National Instruments Vision Development Module function called "IMAQ Inverse FFT". The image is then equalized using a National Instruments Vision Development Module function called "IMAQ equalize". This function generates a histogram equalization of the image. The image's pixel values ​​are redistributed to linearize the accumulated histogram. The acquired grayscale image is equalized and converted to an FFT of the image using a National Instruments Vision Development Module function called "IMAQ FFT". The FFT is then truncated using a National Instruments Vision Development Module function called "IMAQ Complex Truncate". The truncation frequency is set to 50.00%. The function is configured so that the low-pass frequency is truncated.The filtered FFT is inversely transformed back into an image using a National Instruments Vision Development Module function called "IMAQ Inverse FFT". The image is then thresholded using a National Instruments Vision Development Module function called "IMAQ threshold". This function converts the image into a binary image based on a manual threshold. For an 8-bit image, all pixels with intensity between 128 and 255 are set to a value of 1. All pixels with intensity less than 128 are given a value of 0 in the binary image. The image is then filtered using a National Instruments Vision Development Module function called "IMAQ Particle Filter 3". The filter is applied to pixels between 3 and 10,000,000. 2 The area of ​​the particles is set to be retained in the binary image. The area of ​​all particles in the image is then determined using a National Instruments Vision Development Module function called "IMAQ Particle Analysis". The function generates an array of the areas of each particle. A National Instruments LabVIEW function called "Average" is used to calculate the value of "Average Area (Pixels)" or average particle size, which is the ROSA score reported in this invention. Generally, a higher ROSA score indicates a higher level of "applesauce" in the sample. Typically, if the ROSA score is higher than 125 but less than 250, the applesauce deficiency in the laminate is observable under reflected light and is treated as a mild level. If the ROSA score is higher than 250 but less than 600, the applesauce deficiency in the laminate is noticeable under reflected light and is treated as an intermediate level. If the ROSA score is higher than 600, the applesauce deficiency in the laminate is noticeable under reflected light and is treated as a severe level.

[0053]

[0056] The following is a simplified description of how laminated rigid composites can generally be manufactured in combination with an interlayer. The formed interlayer can be placed between two glass substrates, and any excess interlayer can be trimmed from the edges to create an assembly. It is not uncommon to create a multilayer glass panel with multiple polymer interlayers by placing multiple polymer interlayer sheets, or polymer interlayer sheets having multiple layers (or a combination of both), within two glass substrates. Next, air is removed from the assembly by an applicable process or method known to those skilled in the art. For example, by a nip roller, vacuum bag, or another degassing mechanism. Furthermore, the interlayer is partially pressed to the substrate by any method known to those skilled in the art. In the final step, to form a final integral structure, this pre-bonding is made more permanent by a high-temperature, high-pressure lamination process, or by any other method known to those skilled in the art, such as an autoclave (but not limited to this).

[0054]

[0057] As previously mentioned, the present invention is described herein with respect to various interrelated aspects and embodiments, and those skilled in the art will understand and recognize that elements or features used to describe one aspect or embodiment may be applicable and useful when describing other embodiments. Accordingly, the descriptions and disclosures of elements or features of aspects or embodiments of the present invention are expressly relied upon herein to describe and support those elements or features in other aspects or embodiments. More specifically, the descriptions and disclosures of elements or features of the bilayer and / or electromagnetically reflective multilayer intermediate layers of the present invention, such as PVB resin, plasticizers, and plasticized PVB, are expressly relied upon herein to describe and support those elements or features in the laminated glass composites described herein, and vice versa.

[0055]

[0058] The following examples (may be multiple) are provided to illustrate in specific and detail many aspects and advantages of the present invention and should not be construed as limiting its scope in any way. Variations, modifications, and adaptations that do not depart from the spirit of the invention will be readily understood by those skilled in the art.

[0056]

[0059] Exemplary plasticized PVB sheets with a thickness of 0.38 mm (referred to as the “disclosed layer” and shown as DL1-6 in Table 1 below) useful as the second layer in the bilayer of this disclosure, and conventional second layers in a comparative bilayer (referred to as the “conventional layer” and shown as CL1-3 in Table 1 below) were prepared. These plasticized PVB sheets were manufactured by melt-extruding a mixture of 100 parts PVB resin and various amounts of plasticizer, as shown in Table 1. For some of the extruded PVB sheets of the samples, the roughness patterns were embossed on the laminate surface (referred to as 1x in Table 1 below) or both the contact surface and the laminate surface (referred to as 2x in Table 1 below) using a roller with a roughness pattern, as shown in the table. The first layer or reflective layer of the prepared samples was a coated electromagnetic energy reflective film commercially available from Eastman Chemical under trade name XIR® 70.48. The warm shrinkage, DF135, Tg, Mw, and PDI of the plasticized PVB sheet were also measured and are listed in Table 1.

[0057]

[0060] The electromagnetic energy reflective coating side of the reflective film, also called the first layer, is lightly bonded to the contact surface of a pre-formed 0.38 mm thick PVB sheet, also called the second layer, as shown in Table 1, to form a double layer. Next, the laminated surface of the second layer is placed in a glass pane, and then a 0.38 mm thick PVB sheet, the same as that used in the double layer, is placed on the base surface of the reflective film as the third layer. Finally, another glass pane is placed on the laminated surface of the third layer. For the second layer, the surface roughness (Rz and MD Rsm) of the side adjacent to the electromagnetic energy reflective coating side of the reflective layer is determined and listed in Table 1 as Rz_1 and MD Rsm_1, while the surface roughness (Rz and MD Rsm) of the laminated surface is determined and listed in Table 1 as Rz_2 and MD Rsm_2.

[0058]

[0061] The multilayer stack was loaded into a vacuum bag with a target vacuum level exceeding 25 inches Hg. After dwelling at 23°C for 20 minutes, the vacuum bag containing the stack was degassed by processing at 95°C for 20 minutes to form a nearly transparent pre-laminated structure. This pre-laminated structure was then processed in an autoclave at 140°C and 185 psi for 60 minutes to form a multilayer rigid laminated composite. The applesauce level was quantified by the ROSA score by imaging a glass laminate with the electromagnetic energy reflective coating side facing the light source.

[0059] [Table 1]

[0060]

[0062] The present invention has been disclosed in conjunction with a description of specific embodiments, including those currently considered preferred embodiments. However, the detailed description is intended to be illustrative and should not be understood as limiting the scope of this disclosure. Embodiments other than those described in detail herein are also included in the present invention, as will be understood by those skilled in the art. Modifications and variations of the described embodiments can be made without departing from the spirit and scope of the present invention.

[0061]

[0063] Furthermore, it will be understood that any range, value, or characteristic shown for any single component of this disclosure may be used interchangeably with any range, value, or characteristic shown for any other component of this disclosure, where applicable, to form embodiments having the values ​​defined for each component as given herein. For example, a polymer layer may be formed that includes a plasticizer content in any given range, in addition to any given range for residual hydroxyl content, to form many substitutions that are, as appropriate, within the scope of the invention but too cumbersome to enumerate.

Claims

1. A double layer for use as a component for an electromagnetically reflective intermediate layer, wherein the double layer is A first layer including an electromagnetic energy reflective layer, wherein the electromagnetic energy reflective layer includes a base surface and an upper surface, and A double layer comprising a second layer having a thickness of 0.3 to 0.55 mm and containing a PVB resin plasticized with a plasticizer to form a plasticized PVB, wherein the second layer has a contact surface adjacent to the upper surface of the electromagnetic energy reflecting layer, and (a) the second layer has a flow value DF135 of 145 μm or less, and (b) the PVB has a PDI greater than 4.

2.

2. The double layer according to claim 1, wherein the contact surface of the second layer has an Rz value of less than 45 μm.

3. The bilayer according to claim 1, wherein the plasticized PVB has a glass transition temperature of more than 35°C.

4. The bilayer according to claim 1, wherein the PVB resin has a weight-average molecular weight of about 180,000 to about 250,000.

5. The bilayer according to claim 3, wherein the plasticizer is present in an amount of 18 to 40 phr.

6. The double layer according to claim 5, wherein the plasticizer comprises 3-GEH.

7. The double layer according to claim 2, wherein the contact surface of the second layer is a non-embossed surface.

8. The double layer according to claim 1, wherein the first layer has a thickness of about 12 microns to about 125 microns.

9. The polyester substrate has a thickness of approximately 12 microns to approximately 125 microns, as described in claim 8.

10. The double layer according to claim 8, wherein the electromagnetic energy reflective coating has a thickness of about 10 nm to 250 nm.

11. The double layer according to claim 10, wherein the electromagnetic energy reflective coating is a vacuum deposition coating.

12. The double layer according to claim 11, wherein the vacuum deposition coating includes layers in which high refractive index material and low refractive index material are alternately arranged.

13. The double layer according to claim 1, wherein the electromagnetic energy reflective layer comprises at least one metal layer, at least one metal oxide layer, or a combination thereof.

14. The double layer according to claim 1, wherein the electromagnetic energy reflective coating comprises a plurality of metal layers or a plurality of metal oxide layers, or a combination thereof.

15. The double layer according to claim 1, wherein the second layer exhibits a warm shrinkage of 8% or less.

16. The double layer according to claim 2, wherein the second layer further comprises a laminate surface having a surface roughness Rz of at least 20 μm on the side opposite to the contact surface.

17. An electromagnetically reflective multilayer intermediate layer, wherein the intermediate layer is A first layer including an electromagnetic energy reflective layer, wherein the electromagnetic energy reflective layer includes a base surface and an upper surface, A second layer having a thickness of 0.3 to 0.55 mm and comprising a PVB resin plasticized with a plasticizer to form a plasticized PVB, wherein the second layer has a contact surface adjacent to the upper surface of the electromagnetic energy reflecting layer, and A third layer comprising a PVB plasticized with a plasticizer to form a plasticized PVB, wherein the third layer has a contact surface adjacent to the base surface of the energy reflecting layer, (a) The second layer has a flow value DF135 of 145 μm or less, and (b) the second layer has a PDI greater than 4.2 for the PVB.

18. A multilayer rigid laminated composite material An electromagnetically reflective intermediate layer according to claim 17, sandwiched between a first rigid sheet and a second rigid sheet, wherein the multilayer rigid laminated composite material includes the electromagnetically reflective intermediate layer, characterized by a ROSA score of 125 pixels or less.

19. A multilayer rigid laminated composite material A first layer including an electromagnetic energy reflective layer, wherein the electromagnetic energy reflective layer includes a base surface and an upper surface, A second layer having a thickness of 0.3 to 0.55 mm and comprising a PVB resin plasticized with a plasticizer to form a plasticized PVB, wherein the second layer has a laminate surface and an opposing contact surface adjacent to the upper surface of the electromagnetic energy reflective layer, and (a) the second layer has a flow value DF135 of 145 μm or less, and (b) the PVB of the second layer has a PDI greater than 4.2, A third layer comprising PVB plasticized using a plasticizer to form a plasticized PVB, wherein the third layer has a laminate surface and an opposing contact surface adjacent to the base surface of the electromagnetic energy reflecting layer, The first rigid sheet adjacent to the laminate surface of the second layer, and The multilayer rigid laminated composite material includes a second rigid sheet adjacent to the laminate surface of the third layer.